2020
DOI: 10.1093/scan/nsaa094
|View full text |Cite
|
Sign up to set email alerts
|

The neural networks underlying reappraisal of empathy for pain

Abstract: Emotion regulation plays a central role in empathy. Only by successfully regulating our own emotions can we reliably use them in order to interpret the content and valence of others’ emotions correctly. In an fMRI-based experiment, we show that regulating one’s emotion via reappraisal modulated biased emotional intensity ratings following an empathy for pain manipulation. Task based analysis revealed increased activity in the right IFG when painful emotions were regulated using reappraisal, whereas empathic fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 51 publications
2
16
0
Order By: Relevance
“…The right cingulate cortex and insula have been implicated in emotion contagion and emotional empathy [89]. Furthermore, some functional neuroimaging studies have demonstrated the prefrontal cortex, frontal pole, and temporal regions in mediating complex cognitive function, including PT and mentalisation [5,90,91]. Multani et al [5] found a loss of cognitive empathy and emotional detection deficit in AD, bvFTD, and PD that were related to decreased functional connectivity mainly in the right inferior temporal gyrus, frontal pole, paracingulate gyrus, insular, and inferior parietal lobule.…”
Section: Discussionmentioning
confidence: 99%
“…The right cingulate cortex and insula have been implicated in emotion contagion and emotional empathy [89]. Furthermore, some functional neuroimaging studies have demonstrated the prefrontal cortex, frontal pole, and temporal regions in mediating complex cognitive function, including PT and mentalisation [5,90,91]. Multani et al [5] found a loss of cognitive empathy and emotional detection deficit in AD, bvFTD, and PD that were related to decreased functional connectivity mainly in the right inferior temporal gyrus, frontal pole, paracingulate gyrus, insular, and inferior parietal lobule.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, reappraisal resulted in increased connectivity with regions involved in the simulation of other pain, as well as self-pain processing [42]. Activation in the left supramarginal gyrus (SMG) and the right middle frontal gyrus (MFG) was found during empathic watch only, suggesting that these two regions play a critical role and are associated with the process of feeling empathy for the pain of others [41].…”
Section: Neural Network For Pain Empathymentioning
confidence: 98%
“…A study compared activated region with fMRI for empathising with painful vs non-painful scenarios as well as for reappraising painful vs non-painful scenarios. Empathising with painful scenarios was associated with increased connectivity with the mid-cingulate and anterior cingulate cortex (ACC), as well as with the bilateral post-central cortex [41].…”
Section: Neural Network For Pain Empathymentioning
confidence: 99%
“…Based on previous experiments conducted in our lab (Naor et al, 2018(Naor et al, , 2020, we used a set of pictures depicting the faces of ten actor models with different emotional expressions (Blais et al, 2012). The picture stimuli database as well as normative data are available at the following address: http://mapageweb.umontreal.…”
Section: Emotional Intensity Evaluation Taskmentioning
confidence: 99%
“…The emotional expressions were morphed to create a sequential morph of 100 pictures for each character. For detailed information, please see Naor et al (2018Naor et al ( , 2020. In our experiment, six models were used (i.e., three males and three female models), each depicting two emotions (happy and angry) at five levels of intensity (10, 30, 50, 70, and 90%), accounting for a total of 60 exemplars.…”
Section: Emotional Intensity Evaluation Taskmentioning
confidence: 99%